2017
DOI: 10.1208/s12248-016-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Metabolites of Meclonazepam by High-Resolution Mass Spectrometry Using Human Liver Microsomes, Hepatocytes, a Mouse Model, and Authentic Urine Samples

Abstract: Abstract.Meclonazepam is a benzodiazepine patented in 1977 to treat parasitic worms, which recently appeared as a designer benzodiazepine and drug of abuse. The aim of this study was to identify metabolites suitable as biomarkers of drug intake in urine using highresolution mass spectrometry, authentic urine samples, and different model systems including human liver microsomes, cryopreserved hepatocytes, and a mice model. The main metabolites of meclonazepam found in human urine were amino-meclonazepam and ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
(17 reference statements)
1
15
0
Order By: Relevance
“…Based on the chromatographic peak areas determined from the urine samples using LC–HRMS (Figure ), 7‐acetamido‐FNTZ, and mainly 7‐amino‐FNTZ were deemed the main urinary metabolites which remained detectable for up 37 hours after FNTZ intake. These observations are consistent with flunitrazepam and meclonazepam metabolic pattern. However, the window of detection of FNTZ is largely lower that the one observed for the two other benzodiazepines.…”
Section: Resultssupporting
confidence: 90%
“…Based on the chromatographic peak areas determined from the urine samples using LC–HRMS (Figure ), 7‐acetamido‐FNTZ, and mainly 7‐amino‐FNTZ were deemed the main urinary metabolites which remained detectable for up 37 hours after FNTZ intake. These observations are consistent with flunitrazepam and meclonazepam metabolic pattern. However, the window of detection of FNTZ is largely lower that the one observed for the two other benzodiazepines.…”
Section: Resultssupporting
confidence: 90%
“…7,[12][13][14][15] Some are metabolized in vivo to traditional BZs. 7,[12][13][14][15] Some are metabolized in vivo to traditional BZs.…”
Section: Designer Benzodiazepines: a Review Of Published Data And Pubmentioning
confidence: 99%
“…Metabolic profiles of a number of the designer BZs have been characterized by mass spectrometric analysis of human urine samples. 7,[12][13][14][15] Some are metabolized in vivo to traditional BZs. For example, the designer BZ diclazepam is metabolized to lorazepam, and the designer compound cloniprazepam is metabolized to clonazepam.…”
Section: Designer Benzodiazepines: a Review Of Published Data And Pubmentioning
confidence: 99%
“…In this context, a study by Pettersson Bergstrand et al showed the presence of designer benzodiazepines in 40% of urine samples from a routine drug testing laboratory in Sweden that tested positive for benzodiazepines on a cloned enzyme donor immune assay (CEDIA) and negative for 'prescription benzodiazepines' by liquid chromatography tandem-mass spectrometry (LC-MS/ MS) analysis. 10 Whereas in vivo metabolism data of some designer benzodiazepines has been published by various authors, 2,4,[11][12][13][14][15] data on newer compounds are scarce. 16 For timely method development, in vitro metabolism studies using pooled human liver microsomes (pHLM) can be utilized to get spectral data of potential phase I metabolites.…”
Section: Introductionmentioning
confidence: 99%